Mardin Süryanilerinde Belleğin Teolojik-Kültürel Çerçevesi / Theological - Cultural Framework of Memory in Mardin Syriacs - Pekasil, Tahir (Journal of History Culture and Art Research, 2016)
Theological - Cultural Framework of Memory in Mardin Syriacs Abstract In this article, “theological/ritual-cultural framework of memory”, "memory participation tools" "recall figures" will be examined in the case of Mardin Syriac Orthodox Church. "Ritual participation" and "rhythmic repetition" which enables "theological-social inclusion" and "integration", also mobilizes remembering instruments and guarantees protection, revival and transfer of cultural memory. This also ensures continuation of sense of belonging. Priests who are accepted as "vicarious memory" enable participation to memory in church which is a "memory space" mediating to the "transmission of blessing and grace by ritual representation". Priests also by institutionalizing ceremonies and rituals which integrated with music, makes cultural meanings functional. The theme is discussed from the perspective of cultural memory and supported by face to face interviews. Mardin Süryanilerinde Belleğin Teolojik-Kültürel Çerçevesi Öz Bu yazıda, Mardin Süryani Ortodoks Kilisesi örneğinden hareketle “belleğin teolojik/ritüel- kültürel çerçevesi”, “belleğe katılım araçları”, “hatırlama figürleri” ele alınacaktır. “Teolojik ve toplumsal katılımı”, “bütünleşmeyi” sağlayan “ritüel katılım” ve “ritmik tekrar”, hatırlama araçlarını harekete geçirerek kültürel belleğin korunmasını, canlandırılmasını ve aktarılmasını garanti etmekte, aidiyetin devamını sağlamaktadır. Belleğe katılımı sağlayan “vekil hafıza” olarak kabul edilen papazlar, bir “hafıza mekânı” olan kilisede, “inayetin ritüel temsille aktarımına” aracılık yapmakta; “ritüel tasarım” yoluyla müzikle bütünleştirdikleri ayin ve ritüelleri kurumsallaştırarak kültürel anlamlara işlerlik kazandırmaktadırlar. Çalışma konusu, kültürel bellek perspektifinden ele alınmış ve mülakat örnekleri ile desteklenmiştir.